2017
DOI: 10.1016/j.ijid.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus infection as a promoting factor for hepatocellular carcinoma in Cameroon: Preliminary Observations

Abstract: Overall, this study indicates a high prevalence of HEV infection in Cameroonian patients with CLD and HCC. These data suggest either that patients with liver tumors are more susceptible to hepeviral infection or that, in a tropical context, HEV might promote the progression of liver diseases towards tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
1
21
1
Order By: Relevance
“…Recent data produced both in Eastern Asia or sub-Saharan Africa, however, indicate that HEV infection might represent a risk factor of chronic liver disease progression leading ultimately to hepatocellular carcinoma (HCC) (Amanya et al, 2017[2]; Amougou Atsama et al, 2017[3]; Bai et al, 2018[6]; Diwe et al, 2013[9]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent data produced both in Eastern Asia or sub-Saharan Africa, however, indicate that HEV infection might represent a risk factor of chronic liver disease progression leading ultimately to hepatocellular carcinoma (HCC) (Amanya et al, 2017[2]; Amougou Atsama et al, 2017[3]; Bai et al, 2018[6]; Diwe et al, 2013[9]).…”
Section: Discussionmentioning
confidence: 99%
“…The present study was not conducted in the context of an acute superinfection with HEV of patients with an already advanced liver disease, circumstances that understandably increase the risk of brutal decompensation and death (Amougou Atsama et al, 2017[3]; Hamid et al, 2002[12]; Radha Krishna et al, 2009[21]). Our work was instead conducted in the frame of a generally mild chronic liver disease (initial diagnosis) and a context of already distant infection with HEV (presence of IgG, absence of IgM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted by Feldt et al in 2013 reported HEV prevalence of 14.2% in adult HIV‐infected patients. Meanwhile, the study by Amougou et al in 2017 reported a prevalence of 41.8% and 12.6% in hepatocellular carcinoma patients and in nonhepatocellular carcinoma subjects, respectively. Although there is no general population study performed in Cameroon, the report on nonhepatocellular carcinoma subjects indicates a high circulation of HEV as well in the general population.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, it has become evident in recent years that HEV infections can be associated with neurological manifestations [17,18], renal aliments [19], hematological disorders [20] and acute pancreatitis [21]. Furthermore, recent data indicate a link between HEV infection and progression to hepatocellular carcinoma in patients infected with hepatitis B virus (HBV) or hepatitis C virus (HCV) [22,23]. Atsama et al [22] reported significantly higher prevalence of anti-HEV IgG in hepatocellular carcinoma (HCC) patients infected with either HBV or HCV compared with HBV/HCV-infected patients with chronic liver disease but not suffering from HCC [22].…”
Section: Introductionmentioning
confidence: 99%